How the Perceptions towards e-Retailer Image Affect the e-Consumer Behavior: Factors & Procedure Involved - Vivian, Leong Wai San; Yazdanifard, Rashad (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
In this research paper, the author highlighted three main elements that impacted online shoppers as an individual, in such security & privacy matters, individual behavior in relation with convenience and expectations and social influence which all will be further discussed.